AKSARA INCUNG : ARTIKEL REVIEW - Mona Aprilia (UIN Imam Bonjol Padang, 2023)
The incung script is a typical script originating from Kerinci. This script is part of the Surat Ulu script family together with the Surat Ulu and Lampung scripts. The incung script has two versions, namely the Marsden note version, and the Westenenk note version. Manuscripts with incung script are often found in Daluwang, Tanduk, Bambo, and Lontar. The incung script texts in this media are in the form of old prose and poetry, including pantun, which contains issues of literature, religion, law, language, ancestral history and customs. This article is an article and book review from sources related to the Incung script.